2022
DOI: 10.3390/fermentation8030126
|View full text |Cite
|
Sign up to set email alerts
|

Can Supplemented Skim Milk (SKM) Boost Your Gut Health?

Abstract: The incorporation of functional ingredients, such as prebiotics and probiotics in food matrices, became a common practice in the human diet to improve the nutritional value of the food product itself. Worldwide, skim milk (SKM) is one of the most consumed food matrices, comprising all the essential nutrients desired for a balanced diet. Thus, the modulation of the human gut microbiota by SKM supplemented with different well-known functional ingredients was evaluated. Four well-studied prebiotics, fructo-oligos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…A FerMac 260 pH controller was used to maintain the pH between 6.0 and 7.0 (the pH of the chicken cecum) in each vessel [35], and the temperature was kept at 41 • C for 48 h with the help of a water bath. Samples of 10 mL were taken aseptically from each vessel, at 0, 24, and 48 h, and processed according Carvalho et al ( 2022) [36]. The analysis of SCFA and lactate was performed by HPLC.…”
Section: Cecum Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…A FerMac 260 pH controller was used to maintain the pH between 6.0 and 7.0 (the pH of the chicken cecum) in each vessel [35], and the temperature was kept at 41 • C for 48 h with the help of a water bath. Samples of 10 mL were taken aseptically from each vessel, at 0, 24, and 48 h, and processed according Carvalho et al ( 2022) [36]. The analysis of SCFA and lactate was performed by HPLC.…”
Section: Cecum Fermentationmentioning
confidence: 99%
“…The supernatants collected after centrifugation were filtered (0.22 µm) and directly analyzed by HPLC in duplicates, as described by de Carvalho et al (2022) [36]. Lactate, acetate, propionate, butyrate (2 mM to 80 mM), and DMSO (2 mM to 650 mM) were identified and quantified using their corresponding calibration curves.…”
Section: Determination Of Organic Acids Produced During In Vitro Ferm...mentioning
confidence: 99%
“…Separation was performed in the Aminex HPX87Pb column (BioRad, Hercules, CA, USA) with a mobile phase of 0.005 M of sulphuric acid at a flow rate of 0.6 mL/min. Following centrifugation, the supernatants were filtered (0.22 µ m) and immediately analyzed by HPLC in duplicate [25]. Using their matching calibration curves, malic acid, lactate,…”
Section: Organic Acids Sugars and Short-chain Fatty Acids Analysis By...mentioning
confidence: 99%
“…Chromatographic analysis was performed with high-performance liquid chromatography, Agilent 1200 HPLC system with a refractive index (RID) detector (1260 Infinity II, Agilent Technologies; Santa Clara, CA, USA), and diode array detector (DAD) operating at 50 • C. Separation was performed in the Aminex HPX87Pb column (BioRad, Hercules, CA, USA) with a mobile phase of 0.005 M of sulphuric acid at a flow rate of 0.6 mL/min. Following centrifugation, the supernatants were filtered (0.22 µm) and immediately analyzed by HPLC in duplicate [25]. Using their matching calibration curves, malic acid, lactate, acetate, butyrate, ethanol, xylose, mannose, galactose, glucose, arabinose, and fructose were identified and measured.…”
Section: Organic Acids Sugars and Short-chain Fatty Acids Analysis By...mentioning
confidence: 99%
“…Several previous studies have assessed the effect of dairy products on human GM, but many have focused on fermented dairy like yogurt ( Link-Amster et al, 1994 ; Odamaki et al, 2012 , 2016 ; Yılmaz et al, 2019 ; Jie et al, 2021 ) or special dairy products like casein powder ( Beaumont et al, 2017 ) or whey bars ( Reimer et al, 2017 ). Some recent studies showed that cow milk could influence the alpha ( Fernandez-Raudales et al, 2012 ; Shuai et al, 2021 ) and beta diversity ( Aslam et al, 2021 ; Shuai et al, 2021 ) of GM and relative abundance (RA) of some taxa including phyla p_Bacteroidetes and p_Proteobacteria and genus g_Roseburia , g_Lactobacillus , g_Prevotella , g_Bifidobacterium , g_Clostridium , g_Streptococcus , g_Atopobium , g_ Leuconostoc , and g_Veillonella in humans ( Fernandez-Raudales et al, 2012 ; Bendtsen et al, 2018 ; Swarte et al, 2020 ; Aslam et al, 2021 ; de Carvalho et al, 2022 ). However, very few studies have reported cow milk’s effect on human gut bacterial species ( Aslam et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%